Optimization and standardization of the sales process in a service sector company through lean tools - Parodi Estremadoyro, Alonso Alberto (2024)
Introduction: Lead times in the design and implementation of spaces in Lima represent 42% of the causes of customer dissatisfaction in the sales process. Therefore, the research focuses on the optimization of lead times, as they are usually very high in small companies (SMEs) and with non-standardized and therefore inefficient processes. Methods: A model is proposed that delineates a standardization plan for a process. Initially, it is necessary to map the existing state of sales process, recommend a new mapping of the quotation process using Value Stream Mapping (VSM), locate the critical path using Pert-CPM, and identify the activity that is causing the greatest amount of process delay. To make the process of identifying standards simpler, data is then gathered and categorized. After standardizing the sales procedure and validating the proposal with Arena Simulator, the outcomes are assessed. Results: A 20.26% reduction was obtained with respect to the total time of the sales process of the initial model. Then, through the collection of non-consolidated data, it was possible to create a database with standardized items to make customer service more efficient completing two more projects in the same amount of time and reducing 6.26 days the average time of each project. Conclusion: The standardization of the sales process in the case study allows them to optimize and standardize it through a proposed model based on Lean tools. Furthermore, small and medium-sized businesses (SMEs) could adopt and adapt the application of Lean service tools to identify their most inefficient processes.